2003
DOI: 10.1099/jmm.0.04978-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunodominant Helicobacter pylori proteins with reactivity to H. pylori-specific egg-yolk immunoglobulin

Abstract: The importance of hens eggs as a source of specific antibodies (IgY) is well recognized. The protective effect of IgY obtained from hens immunized with Helicobacter pylori whole-cell lysate has been reported for the control of H. pylori infection. However, IgY produced by whole-cell lysates presents the possibility of cross-reactivity with other bacteria, including the normal human flora, and this could decrease the efficiency of IgY. In the present study, the immunodominant proteins of H. pylori with reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 24 publications
3
37
0
Order By: Relevance
“…To address this problem, we identified the following H. pylori proteins as those that reacted immunodominantly to IgY-Hp: UreA, UreB, heatshock proteins (HSP60), probable peroxiredoxin and probable thiol peroxidase (Shin et al, 2003). Of the five immunodominant proteins, urease plays a pivotal role in the pathogenesis of H. pylori infection by protecting the bacteria from the acid environment of the stomach, promoting colonization and inducing the production of ammonia (Bury-Mone et al, 2001;Graham et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To address this problem, we identified the following H. pylori proteins as those that reacted immunodominantly to IgY-Hp: UreA, UreB, heatshock proteins (HSP60), probable peroxiredoxin and probable thiol peroxidase (Shin et al, 2003). Of the five immunodominant proteins, urease plays a pivotal role in the pathogenesis of H. pylori infection by protecting the bacteria from the acid environment of the stomach, promoting colonization and inducing the production of ammonia (Bury-Mone et al, 2001;Graham et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that IgY-Hp was immunodominantly reactive to UreA and UreB (Shin et al, 2003). Using hydropathy plots (Kyte-Doolittle) that covered the entire sequence of H. pylori urease, we selected regions with high hydrophilicity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations